The impact of climate change on water resources in the aspect of global economy - Adamiczka, Hanna (Wpływ zmian klimatycznych na zasoby wodne w aspekcie problemów gospodarki światowej, 2017)
Climate change has been observed for many years, being a worlwide source of concern. Reoccuring droughts and changes in precipitation in some regions of the world prompted research into the influence of climate change on the drying up of water. The following study analyses the dependencies between climate change and the drying up of rivers. In the introduction a history of climate change is presented followed by an analysis of global water reasources: their availability, changes in precipitation and their causes and effects. The third chapter deals with the influence of the observed changes on the availability of freshwater in the world. The study ends with the conclusion that the impact of climate change on the drying up of water remains unclear, with the bigger problem being the impact of these changes on the reduction of the quality of water, a fact that may lead to many global problems.
Biblioteka Regionalisty, 2017, Nr 17, s. 7-18
Keywords: climate change; climate; river; water resources; global economy; warming; zmiany klimatyczne; klimat; rzeka; zasoby wodne; gospodarka światowa; ocieplenie